Bhutan : Public Sector Accounting and Auditing, A Comparison to International Standards - World Bank (Washington, DC, 2012)
The objectives of this report are: (a) to provide the country's accounting and audit authorities and other interested stakeholders with a common well-founded knowledge as to where local practices stand in accordance with the internationally developed standards of financial reporting and audit; (b) to assess the prevailing variances; (c) to chart paths to reduce the variances; and (d) to provide a continuing basis for measuring improvements. The analysis in this report has been conducted in light of the strong measures being taken in the Kingdom of Bhutan to reform the accounting and auditing processes. The report addresses several issues such as: adopting international accounting standards in major public enterprises; implementing professional leadership in accounting and financial management; implementing a fully integrated, computerized government accounting system; drafting new acts on public financial management and combating corruption; strengthening the Royal Institute of Management (RIM); and providing training for finance, accounting, and internal audit staff in line ministries and other government agencies, heads of administration and finance divisions, and other managers.